Assessing periadolescent memory ability and characterizing the development of a functional brain network vulnerable to Alzheimer's disease. (20th December 2022) - Behm, Lillian; Phipps, Connor J; Ramirez, Meghan K; Sexton, Jennifer N; Heller, Abi M; Zatkalik, Abigail L; Nickolas, Kristen; DeCesare, Thomas A; Maerlender, Arthur C.; Phatak, Vaishali S; Cramer, Justin A.; Blair, James; et al.
Abstract: Background: In typically presenting Alzheimer's disease (AD), pathological changes to the hippocampus (Hc) and its associated functional brain networks result in impaired declarative/relational memory. While it is known that risk factors for AD (genetic, environmental, etc.) can impact hippocampal resting‐state functional connectivity (RSFC) later in life, the development of the hippocampus and its connections to other brain regions may also be influenced by such risk factors. The goal the current study was to characterize the neurodevelopmental changes in this hippocampal network during the periadolescent epoch and determine whether the observed changes were associated with declarative/relational memory ability. Therefore, we utilized a cross‐sectional approach to test whether individual differences in hippocampal RSFC covary with outcomes on a test of relational memory ability in periadolescent children. Method: Data were drawn from an ongoing NIA‐funded project: the Polygenic Risk of Alzheimer's Disease in Nebraska Kids (PRANK) study. Our analysis was carried out using data from healthy periadolescent participants (N=90; age 8‐13 years). We assessed declarative/relational memory with Cambridge Cognition's Paired Associates Learning (PAL) task. To conduct the resting‐state functional MRI analyses, we used a seed‐based approach with the bilateral hippocampus as the seed region of interest. We then analyzed the hippocampal RSFC data to and assessed covariance of individual patterns of hippocampal RSFC with memory performance measured with the PAL task. Result: Our preliminary findings, largely consistent with previous work, demonstrate patterns of hippocampal RSFC sharing territory with the ventral and lateral portions of the default mode network (DMN). In addition, we observed evidence of regional covariance between hippocampal RSFC and PAL task performance. Conclusion: The preliminary findings of the ongoing PRANK study indicate that hippocampal RSFC covaries regionally with hippocampal‐dependent memory ability in periadolescent children. Future work from the PRANK study aims to understand whether genetic and polygenic risk factors for AD influence this hippocampal network development. To do so, we will utilize participants' AD polygenic risk scores, and determine whether those scores are related to individual differences in hippocampal RSFC.